Behaviour and analysis of ultra high performance fibre reinforced concrete (UHPFRC) skew slabs. (15th November 2019) - Xie, Tianyu; Mohamed Ali, M.S.; Visintin, Phillip
Highlights: Five UHPFRC slabs with different skewness are tested. Influences of slab skewness on deflection and reaction of UHPFRC slabs are studied. Behaviours of UHPFRC slabs at serviceability and ultimate limits states are investigated. A closed form solution for the actions of UHPFRC skew deck slabs is developed. Yield line analysis is conducted using a novel and generic mechanics based approach. Abstract: This study presents an experimental and theoretical investigation of the performance of ultra-high performance fibre reinforced concrete (UHPFRC) skew bridge decks. Five simply-supported UHPFRC slabs with different skew angles were tested under monotonically increasing concentrated load. It was observed that an increase in the skewness of a slab led to a more unsymmetrical vertical deflection profile, and also resulted in a decrease in the magnitude of reaction forces at the acute corners and a corresponding increase in the reaction forces at the obtuse corners. The test results also show that, although some reduction in ductility was seen with increasing skewness of a slab, the specimen with over 25° skew angle still maintained a desirable load carrying capacity and ductility compared to those of a conventional RC straight slab. In addition to the experimental investigations, a fundamental mechanics based closed-form model was developed based on strain energy theorem to predict the performance of a UHPFRC skew slab under linear elastic material condition. At its ultimate limit state, a novel yield-line analysis using a numerically-generated mechanics based moment-rotation relationship was adopted to predict the ultimate load carrying capacity of a skew UHPFRC slab. Both the generic analytical procedures were compared and against test results obtained from this study, as well as those reported in literature, and the results show that the models developed can be applied to UHPFRC skew slabs.